2021
DOI: 10.1158/1078-0432.ccr-20-4116
|View full text |Cite
|
Sign up to set email alerts
|

Organoid Sensitivity Correlates with Therapeutic Response in Patients with Pancreatic Cancer

Abstract: Purpose: Pancreatic ductal adenocarcinoma (PDAC) remains a significant health issue. For most patients, there are no options for targeted therapy, and existing treatments are limited by toxicity. The HOPE trial (Harnessing Organoids for PErsonalized Therapy) was a pilot feasibility trial aiming to prospectively generate patient-derived organoids (PDO) from patients with PDAC and test their drug sensitivity and correlation with clinical outcomes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…Our own initial findings using monotypic organoid cultures indicate that we may benefit from, including multiple readouts in PDO drug sensitivity and resistance testing. Other groups use a variety of readouts, but the number of organoids and matched patient responses are too low to draw conclusions about the impact of assay parameters on predicting/guiding personalized treatments [51,[53][54][55]64]. Clearly, we must continue to test and validate organoids as a predictive platform for clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our own initial findings using monotypic organoid cultures indicate that we may benefit from, including multiple readouts in PDO drug sensitivity and resistance testing. Other groups use a variety of readouts, but the number of organoids and matched patient responses are too low to draw conclusions about the impact of assay parameters on predicting/guiding personalized treatments [51,[53][54][55]64]. Clearly, we must continue to test and validate organoids as a predictive platform for clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sharick et al [63] found that drug screening results matched clinical data for all of the patients (7/7 PDOs) in their study. Grossman et al found concordance between the ex vivo responses of at least one anticancer agent and the clinical treatment regimen in 12/12 cases [55]. In a study comparing organoids from patients who were administered FOLFIRINOX in the neoadjuvant setting to organoids derived from treatment-naïve patients, the ex vivo PDO responses to FOLFIRINOX were weak/absent in 5 of 5 cases of the neoadjuvant-treated group and robust in 4/5 of the treatment-naïve cases [64].…”
Section: Drug Sensitivity and Resistance Testing And Personalized Medicinementioning
confidence: 97%
See 2 more Smart Citations
“…This makes PDO and PDX models become a hot area of research. Several studies have already reported that PDOs can be used to predict responses in cancer patient in the clinic ( 159 , 160 ). The model that uses the PDO model to conduct high-throughput drug screening and further confirm the response to agents in PDX seems to be promising in facilitating personalized medicine.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%